Pearl Millet: A Climate-Resilient Nutricereal for Mitigating Hidden Hunger and Provide Nutritional Security - Satyavathi, C. Tara; Ambawat, Supriya; Khandelwal, Vikas; Srivastava, Rakesh K. (Frontiers in Plant Science, 2021)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is the 5th most important cereal crop after rice, wheat, maize and sorghum. It is widely grown on 26 million ha in the arid and semi-arid tropical regions of Asia and Africa accounting for almost half of the global millet production. Climate change affects crop production through direct impacts on the biophysical factors such as plant and animal growth and infrastructures associated with food processing and distribution. Assessment of the effects of global climate changes on agriculture might help to properly anticipate and adapt farming to maximize agricultural production. Pearl millet being a climate-resilient crop is very important for minimizing the adverse effects of climate change, hence facilitating income and food security among farming communities of arid regions. Pearl millet has deep root system and can survive in wide range of ecological conditions under water scarcity. It has high photosynthetic efficiency, less irrigational requirements, better growth and productivity in low nutrient input conditions and is less reliant on synthetic fertilizers. These attributes have made it a crop of choice for cultivation in arid and semi-arid regions of the world. A number of hybrids and varieties of pearl millet were developed during last 50 years in India both by public and private sector. Pearl millet is nutritionally superior and rich in several micronutrients and macronutrients especially Fe and Zn and can overcome malnutrition and hidden hunger. Inclusion of minimum standards for micronutrients - grain iron and zinc content in the cultivar release policy is the first of its kind step taken in pearl millet unlike in any crop anywhere in the world moving towards enhanced food and nutritional security. The availability of genome sequence information and several genomic studies for stress tolerance provides good opportunity to further exploit the nutritional and climate resilient attributes of pearl millet. Thus, pearl millet is the next generation crop holding the potential of nutritional richness and the climate-resilience.